The effect of CO2 concentrations and the injection strategy on synechococcus sp. PCC7002 culture - Azmi, Azlin Suhaida; Amid, Azura; Mohamad Puad, Noor Illi; Jamal, Parveen (Malaysian Society for Molecular Biology and Biotechnology, 2017)
Photosynthetic microorganism such as cyanobacteria emerge attractive due to its diverse potential uses in the biotechnology field. It is also useful for CO2 sequestration and biofuel production. However diﬀerent CO2 concentrations supplied to the culture aﬀect cell growth and lipid production in diﬀerent ways. This paper focuses on the inﬂuences of CO2 concentrations (i.e. 15%(v/v) to 30% (v/v)), which was supplied for 30 minutes every day (i.e. total of 7 days of experiment duration) to the culture system, on the growth of Synechococccus sp. (PCC 7002 strain), total lipid production, culture pH and CO2 removal. Te results showed that the highest growth and total lipid were obtained when the culture was supplied with 15%(v/v) and 30%(v/v) of CO2, respectively. Te CO2 removal was decreasing when the concentration was at 30%(v/v). Finally, the pH of cultures reduced as the CO2 concentration increased.